Assesment Dan Perhitungan Struktur Eksisting Bangunan Untuk Penambahan Dua Lantai - Tarigan, Valentana Ardian; Panggabean, Immanuel (Universitas Quality, 2025)
The assessment was carried out to determine the condition of the ex-Jl Brigjen Katamso Sibolga building. The purpose of this assessment is to determine the condition of the existing structure so that it can be considered for development plans for the building. The characteristics of buildings in strong earthquake areas must really pay attention to the effects of earthquakes on buildings. Matters related to the above show the ability of existing buildings to carry design loads which are linked to the dimensions of the building in carrying loads on the structure that occur in various combinations specified in the Indonesian National Standards. Therefore, an in-depth analysis is needed carefully and of course following the applicable building codes. The analysis is carried out using special program tools to calculate the structure. The building can be raised by 2 (two) levels by strengthening the structural parts that have been calculated using Sanspro, namely the pile cap and columns, and reducing additional dead loads such as walls.